Influence of negative ions on ion-acoustic solitary waves in a two-electron-temperature plasma - Chattopadhyay, Shankar (Array, 2009)
Ion-acoustic solitary waves in a drift negative ion plasma have been investigated for two-electron temperatures. Tagare and Reddy studied the effect of higher-order nonlinearity on ion-acoustic waves with cold positive and negative ions for isothermal and non-isothermal electrons using reductive perturbation technique. In this work, we study warm positive and negative ions with two-temperature isothermal electrons using the pseudopotential method. It is found that the concentration of negative ions, drift velocities, mass ratios, equal temperatures of ions (particular case) and presence of two groups of electrons and their ratios modify the profiles of the Sagdeev pseudopotential curves of the solitary waves in the plasma of the first- (f1) and second-order (f2) solitary-wave solutions